Connecting university mathematics and school mathematics to address Klein’s double discontinuity: A case of ring theory - Agnita Siska Pramasdyahsari; Rina Dwi Setyawati; Irkham Ulil Albab (Beta: Jurnal Tadris Matematika, 2019)
[English]: The article aims to reveal how pre-service mathematics teachers (PMTs) identify the connection between ring theory and the mathematics topics in secondary schools in Indonesia. The data was collected from the students' workgroup as a part of course assignments in ring theory course in 6th semester. Through a descriptive qualitative approach, the identified mathematical connections by the PMTs were analyzed through the concept-by-concept framework. The findings show that connection that PMTs made is categorized as concept-by-concept comparison through common features. They could elaborate on the connected topic explicitly at some points and connect the mathematical ideas from ring theory to the school mathematics topics even though they do not reveal all the existing connections. For mathematics educators who teach advanced algebra, the finding could be a reference for designing a course that enables PMTs to be more aware of the mathematical connections which will be beneficial for their future roles as mathematics teachers. Keywords: Mathematical connections, Pre-service mathematics teachers, Ring theory, School mathematics [Bahasa]: Artikel ini bertujuan mengungkap bagaimana calon guru matematika mengidentifikasi koneksi antara teori Ring dengan topik matematika sekolah di Indonesia. Data dikumpulkan dari hasil kerja kelompok siswa sebagai bagian tugas mata kuliah teori Ring pada semester 6. Melalui pendekatan deskriptif kualitatif, koneksi matematika yang diidentifikasi oleh calon guru dianalisis menggunakan kerangka kerja konsep-dengan-konsep. Temuan penelitian menunjukkan bahwa koneksi yang dihasilkan calon guru merupakan kategori perbandingan konsep-dengan-konsep yang masih bersifat umum. Calon guru bisa mengelaborasi beberapa koneksi topik matematika secara eksplisit dan menghubungkan ide matematika dari teori Ring terhadap topik matematika sekolah walaupun belum mengungkap semua koneksi yang ada. Untuk pendidik calon guru matematika yang mengajar aljabar lanjut, hasil penelitian ini bisa menjadi panduan untuk merancang (mata) kuliah yang memungkinkan calon guru lebih sadar terkait koneksi matematika yang akan memberikan manfaat untuk peran mereka sebagai guru matematika. Kata kunci: Koneksi matematika, Calon guru matematika, Teori Ring, Matematika sekolah